2019
DOI: 10.1186/s12864-018-5379-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study reveals novel loci associated with body size and carcass yields in Pekin ducks

Abstract: BackgroundPekin duck products have become popular in Asia over recent decades and account for an increasing market share. However, the genetic mechanisms affecting carcass growth in Pekin ducks remain unknown. This study aimed to identify quantitative trait loci affecting body size and carcass yields in Pekin ducks.ResultsWe measured 18 carcass traits in 639 Pekin ducks and performed genotyping using genotyping-by-sequencing (GBS). Loci-based association analysis detected 37 significant loci for the 17 traits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(173 citation statements)
references
References 50 publications
(48 reference statements)
10
163
0
Order By: Relevance
“…As given in Figure 1 , the estimated heritabilit of BW21 (0.29) and BW42 (0.48) were relatively high; thus, they could be improved by direct phenotypic selection. Previous studies showed that the heritability of body weight at the age of 6 wk lay between 0.32 and 0.64 ( Li et al., 2006 , Deng et al., 2019 ). And Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…As given in Figure 1 , the estimated heritabilit of BW21 (0.29) and BW42 (0.48) were relatively high; thus, they could be improved by direct phenotypic selection. Previous studies showed that the heritability of body weight at the age of 6 wk lay between 0.32 and 0.64 ( Li et al., 2006 , Deng et al., 2019 ). And Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of RNA sequencing libraries were performed at Biomarker Technologies Corporation (Beijing, China) following instructions similar to Guo et al [17]. Briefly, after enrichment and purification with oligo (dT)-rich magnetic beads, mRNA was cleaved into short fragments.…”
Section: Rna Extraction Cdna Library Construction and Illumina Sequementioning
confidence: 99%
“…In recent years, transcriptome sequencing has become an important technique for identifying stress-related genes and finding the multiple biological pathways [16]. It has been successfully used to reveal mechanisms related to abiotic stress responses in many species, such as Chinese kale (Brassica alboglabra) [17], Pyropia haitanensis [18], Chinese cabbage (Brassica rapa ssp. Chinensis) [19], sweet maize (Zea mays L.) [20], spinach (Spinacia oleracea L.) [21], pepper (Capsicum annum L.) [22].…”
Section: Introductionmentioning
confidence: 99%
“…across wheat chromosomes [61][62][63]. A high structural similarity of exon/intron structure between TaPAO3, TaPAO4 and TaPAO5, and their close affinity at the distal end of the long arm of homoeologous group 2 suggest that a gene duplication event might be involved in the evolution of these genes [64].…”
Section: Plos Onementioning
confidence: 99%